Induction of breast cancer stem cells by M1 macrophages through Lin-28B-let-7-HMGA2 axis. (28th June 2019) - Guo, Liang; Cheng, Xiang; Chen, Hongyu; Chen, Changguo; Xie, Shuai; Zhao, Min; Liu, Dan; Deng, Que; Liu, Yanjun; Wang, Xiaomeng; Chen, Xintian; Wang, Jiangong; et al.
Abstract: Proinflammatory macrophage (M1) is now being suggested as a potential therapeutic strategy for cancer because of its tumoricidal capacity. However, few studies have been focused directly on the effects of M1 macrophages on cancer cells. Here, we found that M1 induced a subpopulation of CD44 high /CD24 − / low or ALDH1 + cells with CSC-like phenotypes from different types of breast cancer cells (BCCs) in a paracrine manner. Stat3/NF-κB pathways in BCCs were activated by proinflammatory cytokines, igniting Lin-28B-let-7-HMGA2 axis to induce CSC through epithelial-mesenchymal transition (EMT). Previously, we reported that Stat3-coordinated Lin-28B-let-7-HMGA2 axis initiated EMT in BCCs. Here, inhibition of Stat3/NF-κB pathways or Lin-28B-let-7-HMGA2 axis suppressed EMT/CSCs program. Notably, HMGA2 knockdown directly repressed M1-induced CSC formation and expression of Klf-4 and Nanog. Meanwhile, prolonged coculture with BCCs endowed M1 with M2 properties. M1 supernatant induced CSC from non-stem cancer cells, while M2 supernatant sustained a higher proportion of ALDH1 + cells. Our data suggest that macrophages might modulate CSC formation and maintenance by transferring between M1/M2 phenotype. Given that M1 are being considered as a promising immunotherapy tool, it is important to inhibit their CSC-inducing potential by targeting key molecules and pathways. Highlights: M1 macrophages induce CSCs through EMT process from non-stem breast cancer cells in a paracrine manner. Stat3/NF-κB-activated Lin-28B-let-7-HMGA2 axis regulates M1-induced EMT/CSC formation, with HMGA2 playing a central role. Macrophages contribute to CSC formation and maintenance by orchestrating M1 and M2 phenotype.